A heated debate: The future cost-efficiency of climate-neutral heating options under consideration of heterogeneity and uncertainty - Michael Moritz; Berit Hanna Czock; Oliver Ruhnau (Institute of Energy Economics at the University of Cologne (EWI), 2024)
To tackle climate change, residential heating must become climate-neutral. Which technology cost-efficiently achieves this goal is a complex question, given the heterogeneity of buildings and existing infrastructure, as well as the uncertainty regarding future energy prices and grid fees. This article aims to disentangle this complexity by comparing the future costs of various decentralized and centralized climate-neutral heating options. Using Germany as a case study, we calculate the future levelized cost of eleven heating technologies for different building and settlement types and a wide range of assumptions for uncertain parameters, such as energy prices and infrastructure costs. We find that electric heat pumps are most often the economical choice within the modeled range of inputs when they are deployed either decentrally, in rural areas, or centrally, with heating grids in more urban areas. Hydrogen boilers can also be cost-efficient, mainly in rural areas and in scenarios with low hydrogen prices and grid fees or high electricity grid fees. By contrast, heating with synthetic natural gas seems unlikely to be economical across our broad range of plausible input assumptions.
Keywords: Q40; Q42; Q48; D61; E61; 330; Infrastructure costs; Energy prices; Heat pumps; Hydrogen; Decarbonization; Techno-economic analysis; Levelized costs of heating; Residential heating; Building energy